Design Strategies for Multi-Unit Residential Buildings During the Post-pandemic Era in China - Xu, Yanqing; Juan, Yi-Kai (Frontiers in Public Health, 2021)
Objective: The sudden outbreak of COVID-19 has greatly endangered public health and life safety, leading to new changes in people's housing needs. The purpose of this study is to establish design strategies that are suitable for China's Multi-Unit Residential Buildings (MURBs) in the post-pandemic era, and to identify the users' preferences for these strategies. Methods: This study compiles a set of design requirements by means of a literature review and expert interviews. Three hundred ninety-five online and on-site questionnaires, based on the refined Kano model, were distributed to respondents to reveal their preferences for these strategies. The relationship between the different demographic variables, the preferences of design strategies, as well as the housing unit preferences of home-buyers were also verified by means of an actual project. Results: This study summarizes the four dimensions and 26 design strategies of MURBs in China during the post-pandemic era. These strategies are further extracted into 6 highly attractive, 5 high-value-added and 4 critical quality attributes. In terms of demographic variables, males need more social space, and the elderly need less office space and separate bathrooms in the master bedroom. Due to the impact of the epidemic, people with higher education levels are more required to work at home, and the overall demand for a home working environment is also higher. Conclusion: The home-buyers' preference survey reveals that the housing unit designed based on the refined Kano model is more attractive to home-buyers. The proposed approach can help to provide important and customized decisions to design firms, housing developers, and the government for MURBs planning and strategy formulation in the post-pandemic era in China. More in-depth user surveys in other regions and investigations into the cost assessment of these strategies might be further conducted in the future.